PENGARUH TINGKAT KESEHATAN BANK TERHADAP RETURN SAHAM SELAMA PANDEMI COVID-19 PADA PERBANKAN YANG TERDAFTAR DI BEI - Kurniawati Widi Pratiwi; Maslichah Maslichah; Afifudin Afifudin (Universitas Islam Malang, 2021)
This study aims to explain the impact of bank health on stock returns during the COVID-19 pandemic in banks listed on the IDX. Using indicators of capital adequacy ratio (CAR), return on assets (ROA), operating income from operating expenses (BO/PO), and non-performing loans (NPL). The data used is secondary data obtained from the Investment Gallery, Faculty of Economics and Business, Islamic University of Malang and the official website www.idx.co.id. Sampling was done by using purposive sampling method. The sample of this survey is 27 public banking companies in three quarters. So that obtained a total of 81 samples. The results of this study indicate that the CAR and ROA variables partially have a positive and significant effect on stock returns. BO/PO has a significant negative effect on stock returns. Non-performing loans, on the other hand, do not affect stock returns.Keywords: bank’s health rate; stock return